Effects of intensified insulin treatment on retinal vessels in diabetic patients. Issue 9 (September 1988) - Brinchmann-Hansen, O; Dahl-Jørgensen, K; Hanssen, K F; Sandvik, L
Abstract : Forty-five diabetic patients were randomly assigned to treatment with continuous subcutaneous insulin infusion (CSII), multiple injections (MI), and conventional insulin treatment (CIT). They were prospectively followed up for one year. A computerised scanning microdensitometer was applied on fundus photographs of retinal vessels, and we studied changes in calibres of the blood column (W0) and in width (Wr/W0) and intensity (Ir) of the central 'light reflex'. After six months of improved metabolic control the Ir was reduced in both MI and CSII cases compared with CIT cases (p less than 0.01), indicating haemorrheological changes in the retinas. Within these six months cotton-wool spots appeared in half the patients (n = 15) on CSII and MI, but not in CIT patients. Subjects who developed cotton-wool spots, compared with those who did not, had greater intensities of reflection and larger calibres of vessels at the start of the study (p less than 0.01). On intensifying the treatment they were characterised by a larger fall in hemoglobin A1 (p less than 0.01) and by a larger decrease in Ir on arteries (p less than 0.05) and veins (p less than 0.01). The behaviour of the retinal circulation is different in patients developing transient ischaemic lesions on intensified insulin treatment from its behaviour in those who do not.